Composite slice‐selective adiabatic excitation for prostate MRSI. (16th October 2012) - Arteaga de Castro, C. S.; Luttje, M. P.; van, M.; Luijten, P. R.; van der, U. A.; Klomp, D. W. J.
<x xml:space="preserve">Abstract</x> Higher magnetic field strengths, such as 7 T, offer increased spectral resolution and higher signal‐to‐noise ratio. These properties can be very advantageous for MRSI. In particular, signals that generally overlap at lower fields, such as choline, polyamines and creatine, can be resolved at 7 T. However, higher magnetic field strengths suffer from strong radiofrequency (RF) field nonuniformities. These nonuniformities become even stronger when using surface transceivers, such as an endorectal coil for prostate imaging. In order to obtain uniform excitations for accurate MRSI measurements, adiabatic sequences are therefore recommended. Conventional adiabatic MRS sequences (i.e. localization by adiabatic selective refocusing, LASER) have relatively long TEs, especially when optimized to measure the strongly coupled spins of citrate in the prostate. The semi‐LASER (sLASER) sequence has a significantly shorter TE, although it does not provide adiabatic excitation. Therefore, we propose an adiabatic sLASER sequence that either has a composite adiabatic slice‐selective excitation (cLASER) or a non‐slice‐selective adiabatic excitation (nsLASER), allowing for shorter TEs, whilst maintaining the adiabatic spin excitation. Furthermore, the spatial properties of the composite adiabatic excitation allow for a high slice excitation bandwidth, resulting in negligible chemical shift displacement artifacts. Exclusion of the slice selection can be considered once the field of view extends beyond the transmit field of the RF coil. The use of a transceiver at high magnetic field strengths has shown that the cLASER and nsLASER sequences are suitable for MRSI of the prostate in both phantom and in vivo validations. Copyright © 2012 John Wiley & Sons, Ltd.